Bridging Youth Technology Readiness and Internet of Things (IoT) Adoption in Agriculture: Perceived Benefits and Risks as Mediators in the TRI Framework - Samsudin, M; Sumin, V (RSF Conference Series: Business, Management and Social Sciences, 2025)
The integration of Internet of Things (IoT) technologies in agriculture offers transformative potential for enhancing productivity, efficiency, and sustainability. However, adoption remains limited, particularly among small and medium-scale farmers in Malaysia, due to economic and technological barriers. This study examines youth readiness to adopt IoT in agriculture, emphasizing the mediating role of perceived benefits and perceived risk within the framework of the Technological Readiness Index (TRI). Tertiary-educated youth are considered pivotal in accelerating digital transformation within the agricultural sector due to their exposure to emerging technologies. A quantitative research design was employed, utilizing structured questionnaires distributed to students across tertiary institutions in Melaka. Stratified sampling and simple random sampling techniques were employed to ensure the collection of representative data. The data were analyzed using SPSS and Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that optimism and innovativeness have a positive influence on perceived benefits, which in turn enhance youth readiness to adopt IoT. Conversely, insecurity and discomfort significantly increase perceived risk, reducing readiness. Mediation analysis confirmed that perceived benefits and perceived risk significantly mediate the relationship between TRI dimensions and youth readiness. Perceived risks moderate the relationship between insecurity, discomfort, and youth readiness to adopt IoT in the the agricultural sector. Higher perceived risks amplify feelings of insecurity and discomfort among youth, inhibiting their readiness to adopt IoT technologies in agriculture. The findings underscore the importance of addressing both cognitive and emotional factors in promoting IoT adoption, providing empirical evidence for policymakers and educational institutions to design targeted interventions that foster a technology-driven agricultural workforce.